Insights into Gum Arabic interactions with cellulose: Strengthening effects on tissue paper. (June 2022) - Ferreira, A. Cláudia S.; Aguado, Roberto; Carta, Ana M.M.S.; Bértolo, Raquel; Murtinho, Dina; Valente, Artur J.M.
Abstract: Competitiveness in the market for tissue paper, the only paper grade whose consumption increased during 2020 in Europe, requires seeking viable options to continuously improve its properties. This work explores the combination of gum Arabic, which is a naturally found, biodegradable, cheap and versatile heteropolymer, with bleached cellulosic pulps. Blends of pulps and alkaline gum Arabic (GAb ) were analyzed in terms of their thermal degradation behavior, morphology, water absorptivity and drying rate. It was found that water uptake increased by 23% for the maximum proportion of GAb tested (30%, w/w) and that water desorption followed quasi-zero-order kinetics. Furthermore, these blends were used to prepare light-weight paper handsheets by bulk addition, in which small proportions of GAb (3%) were enough to significantly improve tensile strength. Remarkably, the most unexpected result came from the surface addition of alkaline GAb by spray coating, as the tensile index was increased from 7 to 18 N m g –1 . Overall, even though it was not possible to improve and enhance simultaneously all properties, the use of pre-blended GAb in papermaking revealed significant potential when it comes to increasing strength, a key property in different tissue products, such as multipurpose and kitchen rolls, or even in handtowels. Graphical Abstract: ga1 Highlights: Blending with gum Arabic enhances the water uptake of pulps. The thermal degradation behaviour indicates a plasticizing effect. Gum Arabic increased the tensile index of paper by up to +153%. Spraying with gum Arabic decreased air permeability (–25%). Drawback: this additive consistently displays a negative effect on softness.